STUDY OF ENVIRONMENTAL COMMUNICATION THEORY IN RESEARCH OF NATURAL RESOURCES MANAGEMENT - Heldi Yunan Ardian (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
The recent environmental issues have become an important area of research for further review, especially on issues related  to  sustainability  aspects  that  address  environmental  issues  themselves,  economic  issues  and  social  issues. The use of natural resources, particularly in relation to the field of agriculture, is considered a competition, which raises  discourses  that  emerge  beyond  state  boundaries  and  becomes  a  global  discussion.  Since  communication  is believed to provide a capable platform of facilitating the process of exchanging information, knowledge and  wis- dom, this paper is expected to be the theoretical basis for research related to environmental issues and communica- tion to reach mutual understanding among the stakeholders involved. Theories offered include: environmental com- munication theory and stakeholder theory, supported: critical discourse analysis and stakeholder analysis as an ap- proriate method to answer the reseach question. Keywords: Environmental Communication, Discourse, Sustainability, Stakeholders